Sistem Informasi Inventory Kartu Uang Elektronik Berbasis Web Pada Bank XYZ - Oktaviana, Shinta; Gunawan, Edwin (POLITEKNIK NEGERI JAKARTA, 2023)
With the advancement of technology, it is hoped that people can create innovations that make work more efficient and faster through the creation of conventional systems becoming computerized. Currently, the card inventory system at PT. Bank XYZ still uses a manual system. Due to incorrect data input and slow data updates affecting business processes, the development of the card inventory system through the website was carried out. The waterfall method is used as the development method to ensure that user needs are well identified and documentation is available. The purpose of the manual process being turned digital is to provide better service to customers and employees, and as part of the effort to accelerate digital transformation and e-business implementation in the company